Fundic gland polyps related to diverse aetiologies show subtle morphological differences: a multicentre retrospective study. Issue 5 (7th March 2022) - Kővári, Bence; El Naili, Reima; Pereira, Daniela Vinha; Kumarasinghe, Priyanthi; De Boer, Willem Bastiaan; Jiang, Kun; Pimiento, Jose M; Fukuda, Masahide; Misdraji, Joseph; Kushima, Ryoji; Lauwers, Gregory Y
Abstract : Aims: Fundic gland polyps (FGPs) comprise 66% of all gastric polyps. Although they are usually non‐syndromic, they may be associated with various syndromes, including familial adenomatous polyposis (FAP) or gastric adenocarcinoma and proximal polyposis of the stomach (GAPPS). We aimed to evaluate how histological features relate to distinct FGP subtypes. Methods and results: We performed a retrospective analysis of 118 FGPs from 109 patients for the architecture of fundic glands, microcyst lining, parietal cell hyperplasia and surface foveolar epithelial changes. Age, gender and history of FAP or GAPPS were collected. Based on combinations of histological features, three distinct patterns (A, B and C) of FGPs were delineated and correlated to the aetiologies. Non‐syndromic FGPs were well‐formed polyps composed of disordered fundic glands with intermediate‐sized microcysts typically lined by a mixture of oxyntic and mucin‐secreting cells (73%). Parietal cell hyperplasia (80%) and foveolar surface hyperplasia (78%) were common. FAP‐associated cases demonstrated small microcysts that were predominantly lined by fundic epithelium (77%), with limited parietal cell hyperplasia (27%); foveolar hyperplasia was uncommon. GAPPS‐related polyps were the largest, with prominent, mucin‐secreting epithelium‐lined microcysts (73%). Hyperproliferative aberrant pits were universally present, whereas parietal cell hyperplasia was uncommon. Pattern A was identified in most non‐syndromic FGPs (74%) and in a minority of FAP‐related FGPs (26%). The majority (82%) of FAP‐related FGPs showed pattern B, but only 18% of non‐syndromic FGPs did. Pattern C consisted exclusively of GAPPS‐associated polyps. Conclusions: We conclude that, although FGPs share similar histomorphology, subtle differences exist between polyps of different aetiology. In the appropriate clinical setting, the recognition of these variations may help to consider syndromic aetiologies. Abstract :